The Influence of Brand Image, Reference Group, Product Quality, And Product Variety, On Purchasing Decisions For Herbalife Shake Nutrition Products - Safitri, Nadya Nurindah Ira; Prastiwi, Septi Kurnia (Profesional Muda Cendekia Publishing, 2023)
This study aims to determine the effect of brand image, reference group, product quality, and product variation on purchasing decisions for Herbalife products. The objects studied in this study are Herbalife user consumers who live in Surakarta and have purchased Herbalife products. The sampling technique in this research is to use the non-probability sampling (Purposive Sampling) technique with a sample size of 110 respondents. The dependent variable in this study is the purchase decision. The independent variables of this study are brand image awareness, reference group, product quality, and product variety. The results showed that brand image and product quality had an insignificant effect on purchasing decisions, while reference groups and product variations affected purchasing decisions. Herbalife products have a variety of interesting product types and experience recommendations from family/friends/friends are important determinants of purchasing decisions for Herbalife products.